SOSIOLOGI LINGKUNGAN DAN RISK SOCIETY : PERSPEKTIF PENDIDIKAN KRITIS MASYARAKAT - Abdul Rahmat; Sriharini Sriharini (Ideas Publishing, 2018)
Environment is an interdisciplinary study in the field of sciences. Sociological perspective is a part of environmental analysis and it is very important because the society and the environment are inseparable . By taking of object culture on modern society, this article is a critical analysis of the risk society of that phenomenon. Based on the study of literatures, modernization through mastery of technology and science have created a technocratic society in which the risk of environmental destruction became the disaster for human being.